x - y = 6
x = y + 2
Solve the system of equations by substitution.
(4, -2)
(6, 0)
no solution
coincident

Question

Asked 11/17/2014 6:58:19 AM

Updated 11/24/2014 12:56:37 AM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [11/24/2014 12:56:37 AM]

s

mrh2149|Points 30|

cutyglyde|Points 461|

nami008|Points 334|

nami008|Points 334|

nami008|Points 334|

emdjay23|Points 17219|

emdjay23|Points 17219|

sweetash256|Points 70|

cutyglyde|Points 461|

Question

Asked 11/17/2014 6:58:19 AM

Updated 11/24/2014 12:56:37 AM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [11/24/2014 12:56:37 AM]

Rating

8

There no solution for x - y = 6 , x = y + 2 Solve the system of equations by substitution.

Put equaiton 2 in euqation 1 , we get the result as follows:

x - y = 6 ,

y + 2 - y = 6 ,

2 = 6 ,

2 is can't be equal to 6 ,

So it has no solution .

Put equaiton 2 in euqation 1 , we get the result as follows:

x - y = 6 ,

y + 2 - y = 6 ,

2 = 6 ,

2 is can't be equal to 6 ,

So it has no solution .

Added 11/24/2014 12:45:45 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/24/2014 1:51:38 PM], Rated good by andrewpallarca

8

The solution for 8y - 1 = x , 3x = 2y is (1/11, 3/22) .Solve the system of equations by substitution.

put equation 1 of x = 8y - 1 in equation 2 ;

3(8y - 1) = 2y ;

24y - 3 = 2y ;

22y = 3 ;

y = 3/22 ;

x = 8*3/22 - 1 ;

x = 24/22 - 22/22 ;

x = 2/22 ;

x = 1/11 .

put equation 1 of x = 8y - 1 in equation 2 ;

3(8y - 1) = 2y ;

24y - 3 = 2y ;

22y = 3 ;

y = 3/22 ;

x = 8*3/22 - 1 ;

x = 24/22 - 22/22 ;

x = 2/22 ;

x = 1/11 .

Added 11/24/2014 12:51:08 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/24/2014 1:52:22 PM], Rated good by andrewpallarca

8

The equations 2x - y = c , x + 2y = d are intersecting .

The slope of 2x - y = c is 2 , the slope of x + 2y = d is -1/2 , so 2 lines are perpendicular to each other ,so they are intersecting .

The slope of 2x - y = c is 2 , the slope of x + 2y = d is -1/2 , so 2 lines are perpendicular to each other ,so they are intersecting .

Added 11/24/2014 12:56:34 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/24/2014 1:52:41 PM], Rated good by andrewpallarca

The three-way division of power among the branches of the federal government is known as:
federal system
separation of powers
checks and balances
representative democracy **Weegy:** The three-way division of power among the branches of the federal government is known as: separation of powers. (More)

Question

Expert Answered

Updated 11/13/2014 7:32:43 AM

0 Answers/Comments

The expression 3x² represents
(3x)(3x)
(3)(x)(x)
(3)(x)(2) **Weegy:** 3x times x is equal to 3x^2 **User:** In simplified exponential notation, the expression a²·a -3·a=
1/a
0
1 (More)

Question

Updated 11/17/2014 11:02:44 PM

1 Answer/Comment

a^2·a^-3·a

= a^2*a*^-3

= a^3*a^-3

= a^3*1/a^3

= 1

= a^2*a*^-3

= a^3*a^-3

= a^3*1/a^3

= 1

Added 11/17/2014 10:51:17 PM

This answer has been confirmed as correct and helpful.

The slope of the line whose equation is y - 3 = 0 is
0
3
no slope **Weegy:** The slope of the line whose equation is y -(2/3)=0 is 0. **User:** Find the slope of the line that passes through the points (2, 1) and (-4, -5).
-1
1
7/5 **User:** Find the slope of the line that passes through the points (0, 0) and (-2, -3).
2/3
3/2
-3/2 **User:** The points (2, 1), (3, 3), (4, 5), and (5, 6) are collinear.
True
False **Weegy:** False, not all sets of three points are collinear. **User:** The lines 2x - 3y = 1 and 2x + 3y = 2 are intersecting.
True
False **Weegy:** A.True **User:** If b = 3, then 3x + y = 1 and bx - y = 3 are parallel.
True
False **User:** If a = -12/5, then 5x + 2y = 6 and 3x - ay = 4 are parallel.
True
False **Weegy:** the answer is B.true **User:** Input the equation of the given line in standard form.
The line with m = -3/4 and b = -2.
**Weegy:** The equation of the line with m = -3/4 and b = -2 in standard form is 3x + 4y = -8 **User:** The y-intercept of the line whose equation is 3x + 2y = 7
-3/2
7/3
7/2 **Weegy:** The y-intercept of the line whose equation is 3x + 2y = 7 is 7/2. **User:** Ben has $3.40 consisting of quarters and dimes. How many coins of each kind does he have if he has 22 coins?
Which of the following system of equations represents the word problem if d is the number of dimes and q is quarters?
d + q = 22 and 10d + 25q = 340
10d + 25q = 22 and d + q = 340
dq = 22 and d + q = 340 **Weegy:** d + q = 22 and 10d + 25q = 340- is the system of equations that represents the word problem if d is the number of dimes and q is quarters.
(More)

Question

Updated 11/17/2014 8:01:37 AM

4 Answers/Comments

The slope of the line whose equation is y - 3 = 0 is 0.

Added 11/17/2014 7:55:03 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/17/2014 8:39:30 AM]

The points (2, 1), (3, 3), (4, 5), and (5, 6) are collinear. FALSE.

Added 11/17/2014 7:57:14 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/17/2014 8:40:13 AM]

If b = 3, then 3x + y = 1 and bx - y = 3 are parallel. FALSE.

Added 11/17/2014 8:00:04 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/17/2014 8:40:44 AM]

Evaluate each expression.
3 -2 =
**Weegy:** 3 -2 = 1 **User:** Given A = {1, 3, 5}, B = {2, 4, 6} and C={1, 2, 3, 4, 5, 6}, then A (B C) =
{}
{1, 3, 5}
{1, 2, 3, 4, 5, 6} **Weegy:** (c + 6)^3 = (c + 6)(c + 6)(c + 6); = (c^2 + 6c + 6c + 36)(c + 6); = (c^2 + 12c + 36)(c + 6); = c^3 + 6c^2 + 12c^2 + 72c + 36c + 216; = c^3 + 18c^2 + 108c + 216 **User:** Given that f(x) = x² + 5x, evaluate f(-2).
-6
-14
7 **Weegy:** f(x) = x? + 5x; f(-2) f(-2) = -2^2 + 5(-2) f(-2) = -4 - 10 f(-2) = -14 **User:** Evaluate g(3) if g(x) = 2x + 1.
1
7
24 (More)

Question

Not Answered

Updated 11/17/2014 10:57:42 PM

3 Answers/Comments

3^-2 = 1/3^2 = 1/9 .

Added 11/17/2014 10:53:05 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/17/2014 11:02:31 PM]

Given that f(x) = x² + 5x, evaluate f(-2) = -6 .

f(-2) = (-2)^2+ 5*(-2)

f(-2) = 4 - 10

f(-2) = -6

f(-2) = (-2)^2+ 5*(-2)

f(-2) = 4 - 10

f(-2) = -6

Added 11/17/2014 10:56:38 PM

If g(x) = 2x + 1 , g(3) = 7 .

g(3) = 2*3 + 1

g(3) = 6 + 1

g(3) = 7

g(3) = 2*3 + 1

g(3) = 6 + 1

g(3) = 7

Added 11/17/2014 10:57:42 PM

Simplify 5(x - 2) + 3x
8x - 2
8x - 10
-7x **Weegy:** 5(x - 2) + 3x = 5x - 10 + 3x = 8x - 10 **User:** Simplify 7 - 2(5 - 2x)
-10x + 25
-4x - 3
4x - 3 **Weegy:** 7 - 2(5 - 2x), 7 - 10 + 4x = 4x - 3 **User:** Simplify 3(x + 2) + 4(x - 5) **User:** The substitution method for solving two-order systems involves solving one equation using the terms of the other equation.
True
False (More)

Question

Not Answered

Updated 11/17/2014 8:22:13 AM

2 Answers/Comments

3(x + 2) + 4(x - 5)

= 3x + 6 + 4x - 20

= 7x - 14

= 3x + 6 + 4x - 20

= 7x - 14

Added 11/17/2014 8:15:22 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/17/2014 8:18:48 AM]

The substitution method for solving two-order systems involves solving one equation using the terms of the other equation. TRUE.

Added 11/17/2014 8:16:48 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/17/2014 8:20:25 AM]

34,468,992

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 842 [Total 6715] Ratings 19 Comments 652 Invitations 0 Online

There are no comments.